High hepatitis B seroprevalence and risk factors for infection in pregnant women on the Thailand-Myanmar Border - Banks, T; Kang, J; Watts, I; Tyrosvoutis, M; Min, A; Tun, N; Keereecharoen, L; Simmawong, W; Wanyatip, S; Hanboonkunupakarn, B; Nosten, F; McGready, R (Journal of Infection in Developing Countries, 2016)
Introduction: Infection from Hepatitis B primarily results from peri-partum vertical transmission and the risk increases in the presence of hepatitis B e antigen. We aimed to evaluate a new screening program for hepatitis B in pregnant women as a component of antenatal services in a marginalized population. Methodology: Counseling and screening for hepatitis B screening was offered to all women at the first visit, at Shoklo Malaria Research Unit (SMRU) antenatal clinics on the Thai-Myanmar border. Point-of-care rapid diagnostic tests (RDT) were used throughout the period of evaluation. A certified Thai Public Health laboratory at Mae Sot Hospital verified RDT positive cases using enzyme-linked immunosorbent assay (ELISA) for HBsAb and HBeAg. Risk factors for hepatitis B were identified by data linkage to antenatal care records. Results: There were 523 (8.5%) RDT positive for HBsAg among 6158 women tested (Aug-2012 to April-2014). Of these 373 (96.9%) of 385 sent for confirmation were positive by ELISA i.e. RDT false positive rate of 3.1% (95% CI 1.7- 5.4). The overall confirmed HbsAg prevalence was 8.3% (511/6158) (95%CI 7.6-9.0). HBeAg prevalence was 32.7% (114/350) (95%CI 27.9-37.7) of cases tested. Risk factors for HBsAg positivity included age >25 years (OR 1.24, CI 1.03-1.49, p 0.021) and Karen heritage (OR 1.73, CI 1.39-2.15, p <0.01). Conclusions: High hepatitis B seroprevalence amongst migrants and refugees accessing SMRU antenatal services likely reflects that of Kayin State, Myanmar, and perinatal prevention programs are required. False positive cases with HBsAg RDT complicate what is theoretically a straightforward screening.